Structural Data and Vibrational Spectra of the Copper(II) Complex of L-Selenomethionine - Baran, Enrique José (2005)
A Cu(II) complex of the amino acid L-selenomethionine of stoichiometry Cu(L-SeMet)2, has been prepared and characterized. Crystallographic data were obtained by means of X-ray powder diffractometry and showed that the compound is isostructural with the related complex of L-methionine, Cu(L-Met)2. The structural analogy is also supported by the analysis of the IR and Raman spectra of the complex, which are briefly discussed in comparison with those of free L-selenomethionine.